1999
DOI: 10.1523/jneurosci.19-18-08114.1999
|View full text |Cite
|
Sign up to set email alerts
|

Reversals of Age-Related Declines in Neuronal Signal Transduction, Cognitive, and Motor Behavioral Deficits with Blueberry, Spinach, or Strawberry Dietary Supplementation

Abstract: Ample research indicates that age-related neuronal-behavioral decrements are the result of oxidative stress that may be ameliorated by antioxidants. Our previous study had shown that rats given dietary supplements of fruit and vegetable extracts with high antioxidant activity for 8 months beginning at 6 months of age retarded age-related declines in neuronal and cognitive function. The present study showed that such supplements (strawberry, spinach, or blueberry at 14.8, 9.1, or 18.6 gm of dried aqueous extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
608
3
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 857 publications
(645 citation statements)
references
References 72 publications
26
608
3
8
Order By: Relevance
“…These results show that coffee, in easily achievable amounts, may reduce both motor and cognitive deficits in aging, similar to prior studies with berries (Joseph et al 1999;Youdim et Joseph et al 1999). Furthermore, the neuroprotective benefits seen with coffee in these studies appear to be not due to caffeine alone but instead to the polyphenols and other bioactive compounds in coffee.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results show that coffee, in easily achievable amounts, may reduce both motor and cognitive deficits in aging, similar to prior studies with berries (Joseph et al 1999;Youdim et Joseph et al 1999). Furthermore, the neuroprotective benefits seen with coffee in these studies appear to be not due to caffeine alone but instead to the polyphenols and other bioactive compounds in coffee.…”
Section: Discussionsupporting
confidence: 86%
“…A battery of age-and diet-sensitive tests of psychomotor behavior (Joseph et al 1983;Shukitt-Hale et al 1998;Joseph et al 1999;Youdim et al 2000;Shukitt-Hale et al 2005;Ingram et al 1994) was administered in a random order to the animals during week 6 of treatment. Each test was performed once, separated by a break between tasks.…”
Section: Psychomotor Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…A battery of age-and diet-sensitive tests of psychomotor behavior (Joseph et al 1983Shukitt-Hale et al 1998;Joseph et al 1999;Youdim et al 2000;ShukittHale et al 2005) was administered in a randomized order to the animals at the end of the sixth week of dietary supplementation. Each test was performed once, separated by a break between tasks.…”
Section: Psychomotor Testingmentioning
confidence: 99%
“…The authors of this study relate the observed effects mainly to the rather unspecific antioxidant activity of catechin and other compounds contained in the preparation and fail to give further insights in the mechanisms related to the increase in mitochondrial SOD activity. Other investigators reported an attenuation of age-related decline in cognitive function and loss of behavioral deficits following long-term dietary supplementation with anthocyanidin-rich foods or plant extracts [90,91,216]. The investigators used several neuronal and behavioral parameters including dopamine-release, GTP-activity, calcium buffering in striatal synaptosomes, rod walking tasks and the water maze performance to elucidate possible mechanisms involved [90,91].…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%